GM2 gangliosidosis future treatments 2 - Mark, Brian (Henry Stewart Talks, 2017)
Challenges of HexA delivery with AAV, HexM modelling and interaction with GM2, GM2 clearance by AAV9-Hex vectors, HexM delivery to Sandhoff disease mice